The evisceration of 'truth': a cinematic-psychoanalytic entanglement with the notion of truth in education. Issue 2 (4th March 2021) - Kabgani, Sajad; Sahragard, Rahman
ABSTRACT: In the neoliberal discourse of education, the notion of truth, as a fantasmatic concept, has a pivotal status. In order to actualise its non-existent yet highly captivating utopia of perfection, progress and prosperity, this discourse needs to present a homogeneous picture of human ontology whose needs and desires can be satisfied as far as s/he believes in the envisaged utopia. Analysing the Polish drama film, Ida (2013), from a psychoanalytic-Lacanian perspective, this paper aims to show how a cinematic entanglement with the notion of truth can eviscerate it from its utopian conception. In the film under analysis, the protagonist's mere act of searching for the truth, rather than necessarily finding it, can turn out to be a more constitutive attempt. Accordingly, the paper argues that a subjective entanglement with the notion of truth is constitutive when the subject identifies with her/his ontological lack, in the Lacanian sense of the term.